2015
DOI: 10.1039/c5ra01543j
|View full text |Cite
|
Sign up to set email alerts
|

Improved oral bioavailability of novel antithrombotic S002-333 via chitosan coated liposomes: a pharmacokinetic assessment

Abstract: S002-333, a novel anti-thrombotic agent, exhibits excellent platelet mediated antithrombotic action and subsequently has no effect on the coagulation cascade. However, its oral bioavailability is hampered due to inherent low aqueous solubility. In order to circumvent this issue, chitosan coated liposomes were prepared by an ethanol injection method. S002-333 loaded liposomes (CH-LIP-F9) were reproduced with homogeneous particle sizes. The liposomal formulation was characterized with respect to size and surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Liposomes were discovered in 1965 by Bangham and have become the most successful drug delivery system [1,2]. Since it is known that liposomes can increase the absorption of substances from the gastrointestinal tract (GIT)-shown by Sessa et al in 1970 [3]-the idea for using liposomes for oral drug delivery purposes exists, and has been followed for decades by many research groups [4][5][6][7][8]. The encapsulation of drugs in liposomes has many advantages: In addition to the high encapsulation efficiency of lipophilic and hydrophilic drugs, as well as their high biocompatibility, liposomes protect their cargo from external influences such as enzymatic degradation or premature metabolism [9].…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes were discovered in 1965 by Bangham and have become the most successful drug delivery system [1,2]. Since it is known that liposomes can increase the absorption of substances from the gastrointestinal tract (GIT)-shown by Sessa et al in 1970 [3]-the idea for using liposomes for oral drug delivery purposes exists, and has been followed for decades by many research groups [4][5][6][7][8]. The encapsulation of drugs in liposomes has many advantages: In addition to the high encapsulation efficiency of lipophilic and hydrophilic drugs, as well as their high biocompatibility, liposomes protect their cargo from external influences such as enzymatic degradation or premature metabolism [9].…”
Section: Introductionmentioning
confidence: 99%
“…The inception of novel drug delivery systems has enhanced the anticancer potential of drugs [5,6]. Therefore, in this study, lipid bilayer liposomes (LiP) that can efficiently codeliver both hydrophobic and hydrophilic drugs by co-loading them in their hydrophilic core and hydrophobic lipid vesicles were chosen as for the co-delivery of PTX and UA [5,7,8]. In a recent investigation, it was shown that hybrid nanoconstruct of albumin-PTX hybrid nanoparticle (L-APN) encapsulated in liposome significantly enhanced anticancer effectiveness by increasing the accumulation of PTX in tumor, bio-distribution and pharmacokinetic parameters [9].…”
Section: Introductionmentioning
confidence: 99%